2014
DOI: 10.1302/0301-620x.96b12.33473
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of time to revision and clinical outcomes following revision of metal-on-metal hip replacements for adverse reaction to metal debris

Abstract: We undertook a retrospective cohort study to determine clinical outcomes following the revision of metal-on-metal (MoM) hip replacements for adverse reaction to metal debris (ARMD), and to identify predictors of time to revision and outcomes following revision. Between 1998 and 2012 a total of 64 MoM hips (mean age at revision of 57.8 years; 46 (72%) female; 46 (72%) hip resurfacings and 18 (28%) total hip replacements) were revised for ARMD at one specialist centre. At a mean follow-up of 4.5 years (1.0 to 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 36 publications
4
35
1
Order By: Relevance
“…First, although our cohort size is similar to previous studies [9, 26, 37], some subgroup analyses may have been affected by small numbers. However, given the limited long-term data reported after MoMHR revision, we consider our findings important and recommend these can be used until larger studies become available.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…First, although our cohort size is similar to previous studies [9, 26, 37], some subgroup analyses may have been affected by small numbers. However, given the limited long-term data reported after MoMHR revision, we consider our findings important and recommend these can be used until larger studies become available.…”
Section: Discussionmentioning
confidence: 68%
“…Studies reporting early implant survivorship and patient-reported outcomes after MoMHR revision observed inferior results after pseudotumor revisions [13, 26], single-component revisions [9, 10], and when using another MoM bearing [19, 26]. However, little is known about these endpoints more than 5 years after MoMHR revision.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Poor short-term outcomes have been reported following ARMD revision [10,11] with few studies assessing prognostic factors of outcomes post-revision [53,63,64]. One study attributed improved outcomes following ARMD revision to increased experience and earlier surgery [63].…”
Section: What Is the Threshold For Revision?mentioning
confidence: 99%